145k views
1 vote
Fill in the table using this function rule

Fill in the table using this function rule-example-1

2 Answers

2 votes

Answer:

Explanation:

Y: -4,2,-4,-28

I think thats the answer i did my calculations how i know how to do it and that's what i get.

User RandomThought
by
5.8k points
5 votes

Answer:

8

2

-4

-28

Explanation:

y = -6(-1) + 2

y = 6 + 2

y = 8

y = -6(0) + 2

y = 2

y = -6(1) + 2

y = -6 + 2

y = -4

y = -6(5) + 2

y = -30 + 2

y = -28

User Ashwinsakthi
by
5.6k points